TROPES IN MEDICAL LANGUAGE AS A MEANS OF ENHANCING EXPRESSIVENESS AND ENSURING UNDERSTANDING BETWEEN DOCTOR AND PATIENT - Nodira Salikhova Nurulloyevna (Web of Journals Publishing, 2024)
This study explores the role of tropes in medical language as tools for enhancing expressiveness and ensuring effective communication between doctors and patients. Tropes- figurative language, such as metaphors, analogies, and idioms- can bridge the gap between medical jargon and patient comprehension, thereby improving patient care and outcomes. The study investigates the types of tropes commonly used in medical interactions, their impact on patient understanding, and their potential benefits in fostering empathy and rapport in the clinical setting. The findings indicate that the appropriate use of tropes can lead to improved understanding, trust, and communication between patients and medical professionals.
Keywords: Medical language, tropes, doctor-patient communication, metaphors, patient understanding.